Dynamic simulation of supply and demand balance of critical metals in new energy industry from a multi-entity perspective: Taking lithium as an example - CHEN Jinyu, LIU Junqi, LUO Qian, REN Xiaohang (Ziyuan Kexue)
[Objective] Critical metals serve as important raw materials for energy transition. The rapid development of the new energy industry has led to substantial growth in the demand for critical metals, posing severe challenges to their supply-demand balance. Therefore, investigating how to achieve supply-demand balance of critical metals in China’s new energy industry under future energy transition has become a pressing issue to be addressed. [Methods] Based on a multi-entity perspective and taking lithium as an example, this study employed a scenario analysis approach to construct a dynamic simulation model for supply-demand balance of new energy metals from 2023 to 2050. [Results] (1) Under different technological progress scenarios, simulation of production decisions by primary mining enterprises and recycling enterprises revealed that primary lithium supply showed drastic fluctuations, while recycled lithium supply demonstrated a stable growth trend. Lithium demand from the electric vehicle manufacturing sector grew rapidly from 2023 to 2035 and then stabilized after 2035. For the energy storage device sector, lithium demand reached its peak around 2038. (2) Under supply-side mining technological progress scenarios, the growth of lithium demand followed an S-shaped trend. In the early stage, lithium supply capacity was lower than demand, but with technological progress and production capacity expansion in later stages, supply eventually exceeded demand. (3) Under supply-side recycling technological progress scenarios, the early-stage growth of lithium supply remained relatively moderate, while lithium supply in the later stage gradually approached the lithium demand levels amid fluctuations. [Conclusion] Without relying on technological progress, China’s new energy industry cannot achieve critical metal supply-demand balance in the future. It is necessary to adopt targeted technological progress pathways such as mining and recycling combined with the characteristics of the new energy industry, while strengthening coordination between supply and demand entities, and coordinating the development and utilization of primary and secondary metals to alleviate long-term supply-demand conflicts.